Caracterización y repercusiones del embarazo precoz en las estudiantes del colegio de bachillerato Jorge Enrique Chávez Celi, año lectivo 2015 - Anchundia Ojeda, Adriana Esthefanía (2015)
This degree work is a study on the characterization and impact of early pregnancy in adolescent students, same aims, to determine the social factors that affect pregnancies among students of the College of School Jorge Enrique Chavez Celi.